Primary prevention of acute cardiovascular events by influenza vaccination: an observational study. (20th December 2022) - Davidson, Jennifer A; Banerjee, Amitava; Douglas, Ian; Leyrat, Clémence; Pebody, Richard; McDonald, Helen I; Herrett, Emily; Forbes, Harriet; Smeeth, Liam; Warren-Gash, Charlotte
Abstract: Aims: Previous studies show a reduced incidence of first myocardial infarction and stroke 1–3 months after influenza vaccination, but it is unclear how underlying cardiovascular risk impacts the association. Methods and results: The study used linked Clinical Practice Research Datalink, Hospital Episode Statistics Admitted Patient Care and Office for National Statistics mortality data from England between 1 September 2008 and 31 August 2019. From the data, individuals aged 40–84 years with a first acute cardiovascular event and influenza vaccination occurring within 12 months of each September were selected. Using a self-controlled case series analysis, season-adjusted cardiovascular risk stratified incidence ratios (IRs) for cardiovascular events after vaccination compared with baseline time before and >120 days after vaccination were generated. 193 900 individuals with a first acute cardiovascular event and influenza vaccine were included. 105 539 had hypertension and 172 050 had a QRISK2 score ≥10%. In main analysis, acute cardiovascular event risk was reduced in the 15–28 days after vaccination [IR 0.72 (95% CI 0.70–0.74)] and, while the effect size tapered, remained reduced to 91–120 days after vaccination [0.83 (0.81–0.88)]. Reduced cardiovascular events were seen after vaccination among individuals of all age groups and with raised and low cardiovascular risk. Conclusions: Influenza vaccine may offer cardiovascular benefit among individuals at varying cardiovascular risk. Further studies are needed to characterize the populations who could derive the most cardiovascular benefits from vaccination. Structured Graphical Abstract: Structured Graphical Abstract Graphical summary of the main findings of the self-controlled case series analysis conducted using electronic health records from the Clinical Practice Research Datalink and the Hospital Episode Statistics investigating the association between influenza vaccination and reduced incidence of first acute cardiovascular events.